Dimensi Politik Lingkungan dalam Pembangunan Pembangkit Listrik Tenaga Panas Bumi (PLTPB) Daratei Desa Ulubelu Kecamatan Golewa Kabupaten Ngada - Maria Elisabeth Bupu; Syahrin B. Kamahi; Yonatan H.L.Lopo (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This research examines environmental scarcity caused by the construction of the Daratei geothermal power plant, in Ulubelu Village, Golewa District, Ngada Regency. The focus of this research is political and social factors that influence the geothermal development process. This research tries to examine in more depth and analyze the environmental impacts of geothermal power plants in terms of social and political aspects, with the aim of knowing the environmental impacts of geothermal power plant construction projects in terms of social and political aspects. This research uses qualitative research methods with data collection techniques in the form of observation, documentation and interviews, with subjects selected purposively, namely selecting informants with certain considerations. The results of this research were then analyzed using environmental scarcity theory which was viewed from social and political aspects including demand scarcity, supply scarcity, structural scarcity, environmental regulations, public and social approval, and government intervention. The results of this research are the main factors causing environmental scarcity due to several political aspects in the form of lack of government support and policies in encouraging the use of geothermal energy as well as lack of community participation and transparency in decision making.